A computational tool for microstrip planar filter design - Mahgoub Elsayed, Mazen Hashim (2017)
Filters are very important part of any communication system. Naturally, RF and microwave systems belong to these systems. Microwave filters are needed in a wide range of applications including satellite communications and wireless communications as well as military applications. Planar filters among the other types of Microwave filters have the advantages of small size and portability. Moreover, planar filters are very appropriate for very high frequencies. With the rapid development of the technology in all aspects of our lives and to meet the aggressive project schedule deadlines and quality requirements which are needed by the engineers in the industrial field of planar filters design, the concept of developing software programs to develop planar filters emerges. Another important point, the fact that for both researchers and students it is not that easy to get a well understanding of the microwave concepts as well as its devices from textbooks alone. Through this thesis, an explanation of a tool known as (FILSoft) will be provided. The tool is developed based on Matlab-GUIs. Furthermore, the tool designs Microstrip line filters with experienced engineers’ design quality in a shorter time than by traditional design procedures. FILSoft is a user friendly design tool, the design procedures through this tool start from lumped elements filter up to Microstrip filter. The user just needs to insert the required filter specifications and the design’s material description then all the required results will be displayed including lumped element filter along with Microstrip filter structure and the filter frequency response. The tool is able to design both Butterworth and Chebyshev analytical functions along with the four types of filters; Low Pass Filter (LPF), High Pass Filter (HPF), Band Pass Filter (BPF), and Band Stop Filter